PWE-014 Development of an Optimum Treatment Regimen for Transcutaneous Posterior Tibial Nerve Stimulation for Faecal Incontinence. (4th June 2013) - Thomas, G; Dudding, T; Nicholls, R J; Vaizey, C
Abstract : Introduction: Posterior tibial nerve stimulation (PTNS) is an effective treatment for faecal incontinence (FI). A wide range of PTNS regimens have been reported. The aim of this study was to determine an improved PTNS regimen. Methods: Patients were randomised to either daily or twice weekly unilateral transcutaneous PTNS for six weeks. The investigator was blinded to group allocation. Once completed, further patients were recruited. They received daily bilateral transcutaneous PTNS for six weeks. The primary outcome measure was the change in frequency of FI episodes per week. PTNS was self-administered by each patient from home. Results: Thirty patients received either daily or twice weekly PTNS. The daily unilateral PTNS group achieved a reduction in frequency of incontinent episodes of 5(11.3) to 3.5(4.31), p = 0.025. Three achieved complete continence. No change was seen in the twice weekly group. Neither group improved deferral time. A further 20 patients received daily bilateral PTNS. They achieved a reduction in frequency of incontinent episodes of 6 (8.25) to 2 (7.25), p = 0.029. Two achieved complete continence. There was an increase in deferral time, 3 (4) to 5 (8) minutes, p = 0.027. Conclusion: Daily bilateral transcutaneous PTNS is an effective treatment for FI. It can be easily self-administered from home. Disclosure of Interest: None Declared.